Current Aspects of Professional Training for Special Education Specialists in the Modern World - Zviekova, Svitlana (Journal of Danubian Studies and Research, 2023)
In the modern educational context, the professional training of specialists in the field of special education plays a particularly crucial role. The increasing number of individuals with special educational needs presents specialists with challenges that require not only a deep understanding of psychological and pedagogical aspects but also up-to-date knowledge and flexibility in addressing various tasks. This article explores the current aspects of professional training for special education specialists in the modern world. The aim of the article is to highlight current trends in the field of special education and the preparation of professionals to respond to contemporary challenges. In examining these aspects, we emphasize the importance of continuous development and adaptation in the field of special education to ensure high-quality support for children and individuals with special needs.